Influência da adição no comportamento reológico da pasta autoadensável de alto desempenho - Rodrigues Piovezam, Igor Andre [UNESP]; Meleiro, Leandro Parras [UNESP]; Isa, Mario Morio [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2008)
Influence of admixture on the rheological behavior of high performance self-compacting paste. This research proposes to study the influence of the specific area, mould and surface texture of admixtures on the rheological behavior of high performance self-compacting paste (HPSCP). The selected admixtures are calcareous filler and basalt filler, which are industrial residues, thus contributing to sustainable development. The paste is made up of cement, silica fume, calcareous filler or basalt filler, water and superplasticizer additive. For this study, the water/cement ratios are fixed = 0.40 L kg(-1); silica fume/cement = 0.10 kg kg(-1); the filler/cement and superplasticizer/cement ratios are determined through Marsh cone and mini-slump tests. The results show that for same filler/cement ratios, the ratios of superplasticizer to paste with calcareous filler are significantly lower than those of paste with basalt filler. The results show that the specific area, mould and surface texture of these admixtures significantly influence the rheological behavior of HPSCP.
Influence of admixture on the rheological behavior of high performance self-compacting paste
Keywords: self-compacting concrete; paste composition; specific area; fluidity; cohesion and sustainable development